العوامل المؤثرة على لغة الأم في اكتساب اللغة العربية للطلاب الجد في معاهد دار النجاح الإسلامية بجاكرتا - Islami, Azmi; Abdullah, Achmad Farouq; Ibrohim, Busthomi; Saputra, Faisal Reza (al-Ittijah : Jurnal Keilmuan dan Kependidikan Bahasa Arab, 2025)
Learning and teaching a foreign language is challenging, but research has developed effective methods to teach it in a short time with reasonable effort. The difficulty of acquiring a language depends on the learner's age and environment. Children need more time than adults, and learners in a language’s native environment require less time than those in unfamiliar environments. This study investigates how the mother tongue influences Arabic language acquisition among new students at Darunnajah Islamic Boarding School in Jakarta. This research aims to analyze the factors that lead to the influence of the mother tongue on acquiring the Arabic language. The researcher used a qualitative approach for this study, and the data collection method for this research is divided into three sections: observation, interviews, and documentation. The findings identify three main factors: (a) internal factors (psychological), such as stress and motivation, which affect language acquisition, with each student's motivation differing due to the language's novelty; (b) external factors (linguistic environment), where the environment plays a key role in motivating students, including interactions with teachers, senior students, and staff; and (c) the curriculum, which must align with the needs of beginner students learning Arabic.